Kompleksitas communication failure: Analisis faktor internal dan eksternal ATC di Bandara Internasional Soekarno-Hatta - Rangkuti, Ismaliyah Yusuf; Novianti, Evi; Aristi, Nindi (Universitas Negeri Malang, 2025)
The complexity of communication failure: An analysis of internal and external factors of ATC at Soekarno-Hatta International Airport Research This research aims to analyze the complexity of communication failure between the Air Traffic Controller (ATC) and the pilot in the Jakarta Flight Information Region (FIR) airspace, with a focus on the internal and external factors that influence it. internal and external factors that influence it. Communication failure in aviation is a serious threat to safety and efficiency, especially in congested airspace such as the Jakarta FIR. Research This research utilized a qualitative approach with a case study method, which involving in-depth interviews with 17 resource persons from the Jakarta Air Traffic Service Center (JATSC), on-site observations, as well as a review of documents and secondary sources. documents and secondary sources. The results show that communication failure is communication failures are influenced by a complex interaction between internal factors such as capacity and readiness of ATC personnel, reliability of communication technology, implementation of operational procedures, as well as the psychological condition of the officers; and external factors such as external factors such as air traffic density, extreme weather conditions, noisy work environment, and interagency coordination. Types of communication failure found include total and partial communication failure, radio interference, transponder damage, blackouts, and pilot interpretation errors. pilot misinterpretation. Understanding these dynamics is important in designing adaptive mitigation strategies to ensure flight safety. Penelitian ini bertujuan untuk menganalisis kompleksitas kegagalan komunikasi (communication failure) antara Air Traffic Controller (ATC) dan pilot di wilayah udara Jakarta Flight Information Region (FIR), dengan fokus pada faktor-faktor internal dan eksternal yang mempengaruhinya. Kegagalan komunikasi dalam penerbangan merupakan ancaman serius terhadap keselamatan dan efisiensi operasional, terutama di wilayah udara padat seperti FIR Jakarta. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, yang melibatkan wawancara mendalam dengan 17 narasumber dari Jakarta Air Traffic Service Centre (JATSC), observasi langsung di lokasi, serta kajian terhadap dokumen dan sumber sekunder. Hasil penelitian menunjukkan bahwa kegagalan komunikasi dipengaruhi oleh interaksi kompleks antara faktor internal seperti kapasitas dan kesiapan personel ATC, keandalan teknologi komunikasi, pelaksanaan prosedur operasional, serta kondisi psikologis petugas; dan faktor eksternal seperti kepadatan lalu lintas udara, kondisi cuaca ekstrem, lingkungan kerja yang bising, serta koordinasi antarinstansi. Jenis kegagalan komunikasi yang ditemukan meliputi total dan partial communication failure, gangguan radio, kerusakan transponder, pemadaman komunikasi (blackout), dan kesalahan interpretasi oleh pilot. Pemahaman terhadap dinamika ini penting dalam merancang strategi mitigasi yang adaptif untuk menjamin keselamatan penerbangan.